CALCULATION OF ELECTRIC FIELD STRENGTH IN THE IONOSPHERIC F-REGION - Yesil, Ali; Kurt, Kadri (Vinca Inst Nuclear Sci, 2018)
In this study, we have calculated the electric field strength, E-y of a plane electromagnetic wave with frequency, omega, propagation along z-axes and the polarized y-axes in 1-D by using Wentzel, Kramers, and Brillouin method for both with and without collision conditions in ionospheric F-region with regard to seasonal and local time. Also, the refractive index of ordinary wave and attenuation factor was computed for collision and collision-free conditions. When the collisions were calculated in the F-region of the ionosphere, it was observed that the electric field strength decreased for all seasons and E-y increased between 275-400 km altitudes encountering approximately hmF2 the peak of F2 for the accepted conditions.
Keywords: electric field strength; jonospheric plasma; Wentzel; Kramers; Brillouin method